Clinical Decompensation and Outcomes in Patients With Compensated Cirrhosis and a Hepatic Venous Pressure Gradient ≥20 mm Hg. (21st October 2020) - Jindal, Ankur; Bhardwaj, Ankit; Kumar, Guresh; Sarin, Shiv Kumar
Abstract : INTRODUCTION: Hepatic venous pressure gradient (HVPG) of ≥10 mm Hg predicts clinical decompensation (CD) in compensated cirrhosis. A proportion of cirrhotic patients at presentation have high HVPG (≥20 mm Hg) and are compensated. The natural history, spectrum of CD, and mortality in this group is largely unknown. METHODS: Consecutive compensated cirrhotic patients with HVPG ≥6 mm Hg (n = 741) were followed up for 3–6 months for the development of any CD. Patients were classified based on the baseline HVPG (6 to <12 mm Hg [low HVPG, Gr.A, n = 163], 12 to <20 mm Hg [intermediate HVPG, Gr.B, n = 437] and ≥20 mm Hg [high HVPG, Gr.C, n = 141]). We analyzed the predictors of first CD, HVPG response to carvedilol, and mortality in these groups. RESULTS: CD developed in 217 (29.3%) patients during a mean follow-up of 1.6 ± 0.4 years, and those who developed CD had higher baseline HVPG (17.02 ± 4.79 vs 14.28 ± 4.86; P < 0.001). First CD was seen earlier (1.3 ± 0.7 years vs 1.5 ± 0.6 years and 1.6 ± 0.5 years, P = 0.02) and more frequently (44.7% vs 11% and 31.1%, P < 0.01) in high HVPG groups compared with low and intermediate HVPG groups, with higher mortality rates. Patients in the high HVPG group compared with the low HVPG group more often had NASH-cirrhosis (35.5% vs 19.6%; P 0.001), higher liver stiffness values (45.06 ± 20.46 vs 20.09 ± 5.47 kPa, P < 0.001), and lower platelet counts (113.37 ± 72.57 vs 151.7 ± 87.30/cmm, P < 0.001). Patients with HVPG ≥12 mm Hg received carvedilol, and a repeat HVPG performed in a proportion after 9.3 ± 2.4 months showed response (≥20% reduction in HVPG or <12 mm Hg) in 31.6% patients (Gr. B, 44.9% > Gr. C, 22.2%, P < 0.05). Baseline HVPG (HVPG ≥12 to <20 mm Hg [Hazard ratio: 2.73] and HVPG ≥20 mm Hg [Hazard ratio: 4.48], P < 0.001) independently predicted CD. DISCUSSION: HVPG ≥20 mm Hg in patients with compensated cirrhosis independently predicts early and more frequent CD and poor outcomes. These patients should be labeled as "high-risk compensated cirrhosis, " and early and effective interventions to reduce portal pressure should be initiated to improve long-term outcomes.